Fitoremediasi Logam Berat Cr Menggunakan Eceng Gondok Eichornia crassipes pada Buangan Limbah Cair Tambang PT. Bukit Makmur Istindo Nikeltama (Bumanik) - Dan Try Borrong; Fahruddin Fahruddin; Anwar Daud (Jurnal Ilmu Alam dan Lingkungan, 2021)
The aim of the study is to determine the effect of water hyacinth in absorbing the content of heavy metal in mine liquid waste of Bukit Makmur Istindo Nikeltama. This type of research was an experiment using quantitative descriptive analysis in the from of field data collection, laboratory data processing, and direct observation of phytoremediation process of water hyacinth with several variations in the number of plants including 15,10,5 plants and control tubs observed for 12 days. The variables observed in this study were Cr, BOD, COD, pH and TDS. The results showed that water hyacinth is effective to reduce mine liquid waste. The value of each variable obtained on the 12th day is still under the quality standard that has been set. In treatment I, the addition of 15 water hyacinth plants produces concentration values of Cr :